The Antitumor Effect of Xihuang Pill on Treg Cells Decreased in Tumor Microenvironment of 4T1 Breast Tumor-Bearing Mice by PI3K/AKT~AP-1 Signaling Pathway. (23rd April 2018) - Li, Xin-ye; Su, Liang; Jiang, Yi-ming; Gao, Wen-bin; Xu, Chun-wei; Zeng, Chang-qian; Song, Jie; Xu, Yu; Weng, Wen-cai; Liang, Wen-bo
Abstract : To study the antitumor effect of Xihuang pill (XHP) on the number of Treg cells in the tumor microenvironment of 4T1 breast tumor-bearing mice by PI3K/AKT/AP-1 pathway, a mouse model was established. Flow cytometry (FCM) and immunohistochemistry (IHC) were used to detect the number of Treg cells in the tumor microenvironment; terminal deoxynucleotidyl transferase dUTP nick end labeling (TUNEL) was used to detect the apoptosis of Treg cells in tumor microenvironment. Quantitative real-time PCR (RT-qPCR) was used to detect the mRNA expression of PI3K, AKT, and AP-1 in Treg cells in tumor microenvironment; immunofluorescence (IF) and Western Blot (WB) were used to detect the protein expression of PI3K, AKT, and AP-1 in Treg cells in tumor microenvironment. Compared with the naive control group, the tumor weight in XHP groups decreased significantly (P < 0.05 ); FCM and IHC results showed that the number of Treg cells in the tumor microenvironment decreased with the dose of XHP groups (P < 0.05 ); TUNEL staining showed that the number of Treg cells in tumor microenvironment increased with the dose of XHP groups (P < 0.05 ); RT-qPCR results showed that the mRNA expression of PI3K and AKT in Treg cells decreased with the dose of XHP groups, while RNA expression of AP-1 increased with the dose of XHP groups (P < 0.05 ); IF and WB results showed that the protein expression of PI3K and AKT in Treg cells decreased with the dose of XHP groups and the protein expression of AP-1 increased with the dose of XHP groups (P < 0.05 ). The results suggested that XHP decreased the number of Treg cells via inhibiting PI3K and AKT expression and upregulating AP-1 expression in Treg cells and then promoting the apoptosis of Treg cells. Thus, XHP could improve the immunosuppressive state of tumor microenvironment and reverse the immune escape to inhibit tumor growth.